2016
DOI: 10.1021/acs.jproteome.5b01019
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Proteomics Implicates a Role for Multiple Secretion Systems in Electrode-Respiring Geobacter sulfurreducens Biofilms

Abstract: Abstract.Geobacter sulfurreducens is a dissimilatory metal-reducing bacterium capable of forming thick electron-conducting biofilms on solid electrodes. Here, we employ for the first time comparative proteomics to identify key physiological changes involved in G. sulfurreducens adaptation from fumarate-respiring planktonic cells to electron-conducting biofilms.Increased levels of proteins involved in outer membrane biogenesis, cell motility and secretion are expressed in biofilms. Of particular importance to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 62 publications
0
10
0
Order By: Relevance
“…Transcriptomic and proteomic analyses have previously been performed to identify important genes for EET in G. sulfurreducens ( Holmes et al, 2006 ; Ding et al, 2008 ; Nevin et al, 2009 ; Aklujkar et al, 2013 ; Kavanagh et al, 2016 ). Here, we compared important genes (including previously reported genes or those identified in this study) for EET in G. soli and G. sulfurreducens at both transcript and translation levels.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Transcriptomic and proteomic analyses have previously been performed to identify important genes for EET in G. sulfurreducens ( Holmes et al, 2006 ; Ding et al, 2008 ; Nevin et al, 2009 ; Aklujkar et al, 2013 ; Kavanagh et al, 2016 ). Here, we compared important genes (including previously reported genes or those identified in this study) for EET in G. soli and G. sulfurreducens at both transcript and translation levels.…”
Section: Discussionmentioning
confidence: 99%
“…However, a number of other c -Cyts and PilA proteins that were upregulated in G. sulfurreducens were unchanged in G. soli (Supplementary Figure S4a ). Comparative proteomics of G. sulfurreducens indicated that proteins associated with multiple secretion systems, such as PulQ and PulE, are particularly important for electron-conducting biofilms vs. planktonic cells (Supplementary Figure S4b ) ( Kavanagh et al, 2016 ). However, these proteins, with the exception of the Type IV pilus secretion lipoprotein PilQ, were unchanged in G. soli .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Flagella—such as FliC, a Geobacter UDPI in the present study—have been associated with biofilm proliferation [ 91 ] as well as with current generation [ 79 ] or dissimilatory respiration of iron oxides by Geobacter [ 92 ]. Future work could take a strain-resolved proteomics approach [ 93 ] to comparing protein expression in BESs by Geobacter in pure culture [ 27 ] or as a dominant member of a constrained community to that as part of a diverse consortium. Such an approach could identify differences in the role of Geobacter role or mechanisms of action when involved with different types of communities, and perhaps identify mechanisms of antagonism against competitors, especially during MFC startup.…”
Section: Discussionmentioning
confidence: 99%
“…These “meta-proteomics” studies have identified metabolic mechanisms behind multispecies fermentation [ 23 ], methanogenesis [ 24 ], or community response to a toxic perturbation [ 25 ]. A few studies have used proteomics methods to investigate electricity generation by model species or isolates [ 26 , 27 ]. Meta-proteomics examinations of BES systems, however, have been limited to a single investigation of protein expression of biocathode biofilm organisms under optimal and suboptimal conditions [ 28 ].…”
Section: Introductionmentioning
confidence: 99%